Предмет: Математика,
автор: arsenmahaev0
2) [3(x + 2y) - y - 27 = 0,
14(x + y) - 3x – 23 = 0;
Ответы
Автор ответа:
3
Ответ:
3(x + 2y) - y - 27 = 0
4(x + y) - 3x - 23 = 0
3x + 6y - y = 27
4x + 4y - 3x = 23
3x + 5y = 27
x + 4y = 23
3x + 5y = 27
x = 23 - 4y
69 - 12y + 5y = 27
x = 23 - 4y
-7y = -42
x = 23 - 4y
y = 6
x = -1
Ответ: y = 6, x = -1
Пошаговое объяснение:
Похожие вопросы
Предмет: Русский язык,
автор: Tanyafka
Предмет: Русский язык,
автор: kira1510
Предмет: Русский язык,
автор: revolutionmys
Предмет: Химия,
автор: Vavchai
Предмет: Математика,
автор: Анжелина11Аджика11